Heterogeneity in patterns of helminth infections across populations of mountain gorillas (Gorilla beringei beringei) - Petrželková, Klara J; Uwamahoro, Carine; Pafčo, Barbora; Červená, Barbora; Samaš, Peter; Mudakikwa, Antoine; Muvunyi, Richard; Uwingeli, Prosper; Gilardi, Kirsten; Nziza, Julius; Noheri, Jean Bosco; Eckardt, Winnie; et al. (Scientific reports, 2021)
Conservation efforts have led to the recovery of the endangered mountain gorilla populations. Due to their limited potential for spatial expansion, population densities increased, which may alter the epidemiology of infectious diseases. Recently, clinical gastrointestinal illnesses linked to helminth infections have been recorded in both gorilla populations. To understand drivers and patterns of helminth infections we quantified strongylid and tapeworm infections across both Virunga Massif and Bwindi populations using fecal egg counts. We assessed the impact of age, sex, group size, season and spatial differences used as a proxy, which reflects observed variation in the occurrence of gastrointestinal problems, vegetation types, gorilla subpopulation growth and associated social structure on helminth infections. We revealed striking geographic differences in strongylid infections with higher egg counts mostly in areas with high occurrences of gastrointestinal disease. Increased helminth egg counts were also associated with decreasing group size in some areas. Observed spatial differences may reflect mutual effects of variations in subpopulation growth rates, gorilla social structure, and vegetation associated with altitude across mountain gorilla habitat. Helminth infection intensities in Virunga gorillas were lowest in the youngest and the oldest animals. Elucidating parasite infection patterns of endangered species with low genetic diversity is crucial for their conservation management.
Keywords: California; nemoci lidoopů; Female; biologická variabilita populace; Biological Variation, Population; Animals; ženské pohlaví; Helminthiasis, Animal; mužské pohlaví; Male; Kalifornie; Parks, Recreational; zvířata; veřejné parky; helmintózy zvířat; Ape Diseases